Blowing in the Wind: Using a Consumer Drone for the Collection of Humpback Whale (Megaptera novaeangliae) Blow Samples during the Arctic Polar Nights - Gomes Costa, Helena Sofia; Rogan, Andrew; Zadra, Christopher; Larsen, Oddbjørn; Rikardsen, Audun H.; Waugh, Courtney Alice (Drones, 2023)
Abstract Analysis of cetacean blow offers a unique potential for non-invasive assessments of their health. In recent years, the use of uncrewed aerial vehicles (UAVs) has revolutionized the way these samples are collected. However, the high cost and expertise associated with purpose-built waterproof UAVs, paired with the challenges of operating during difficult meteorological conditions, can be prohibitive for their standardized use worldwide. A pilot study was conducted in a Northern Norwegian fjord during winter, to assess the feasibility of using a minimally modified and affordable consumer drone to collect blow samples even during the polar nights’ challenging weather conditions. For each flight, six petri dishes were attached with velcro to a DJI Mavic 2 Pro. The flights were conducted under temperatures ranging from -1 to -18 degrees Celsius, wind speeds ranging from 9 to 31 km/h, and with the absence of the sun. During the 6-day-long boat survey, 16 blow samples were successfully collected from 11 distinct groups of humpback whales (Megaptera novaeangliae). With this study, we further validated the use of a consumer drone as a practical, affordable, and simplified tool for blow collection, functional under harsh meteorological conditions.